What underlies sex differences in heart failure onset within the first year after a first myocardial infarction? - Leboube, Simon; Camboulives, Louise; Bochaton, Thomas; Amaz, Camille; Bergerot, Cyrille; Altman, Mikhail; Loppinet, Thomas; Cherpaz, Maelle; Monsec, Thierry; Sportouch, Catherine; Trinh, Annie; Soulier, Camille; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Women are more likely to develop heart failure (HF) after myocardial infarction.However, diagnosis and re-perfusion are often delayed.Objectives: To compare the prevalence of HF after PPCI-treated STEMI between sexes and to study its associations with co-morbidities, infarct size and left ventricular (LV) systolic and diastolic dysfunctions (DD).Methods: Patients with PPCI-treated anterior STEMI, from the CIRCUS study cohort were followed up for one year and HF events were recorded. Evaluation of ejection fraction (LVEF) and DD were performed at baseline and at one year. Elevated LV filling pressure (LVFP) included grade 2 and 3 DD.Results: Out of 791 patients from the CIRCUS study, 135 were women. At one year, proportion of patients developing HF was 21% in men and 34% in women (p = 0.001). In the subset of 407 patients with available diastolic parameters the rate of HF was also higher in women. HF during the initial hospitalization was comparable between sexes. But, women had a higher incidence of rehospitalization for HF within the first year after STEMI (14.1% vs 4.1%, p = 0.005). Women were older with a higher prevalence of hypertension. Infarct size and LVEF were similar between sexes. Elevated LVFP was observed more frequently in women than in men during the initial hospitalization and at 1 year (26% vs 12%, p = 0.04 and 22% vs 12%, p = 0.006 respectively). Interestingly, only initial elevated LVFP (HR 5.9 95% CI (2.4-14.5), p < 0.001), age and hypertension were independently associated with rehospitalization for HF.Conclusions: After PPCI-treated anterior STEMI, despite comparable infarct size and LVEF, women presented a higher proportion of rehospitalization for HF than men. That was likely due to a greater DD associated with older age and hypertension.